2022
DOI: 10.3390/w14071168
|View full text |Cite
|
Sign up to set email alerts
|

Local Scour around Tandem Double Piers under an Ice Cover

Abstract: Compared to the scour around a single pier, the local scour process around tandem double piers is much more complicated. Based on laboratory experiments in a flume, we conducted the scour process around tandem double piers under an ice-covered flow condition. The results showed that when the pier spacing ratio L/D = 2 (where L = the pier spacing distance, and D = the pier diameter), the rear pier (the downstream one) will intensify the horseshoe vortex process behind the front pier, and the scour depth around … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…In order to avoid the sand bed at the entrance/exit boundary from being scoured by the approach flow, the high and wide scour prevention plates of equal height were laid in the front and rear sections of the model sand bed as the bed fixing area, and their surface roughness was consistent with that of the sand bed. The model of the bridge pier in the dynamic-bed test section for the field mea ments was based on the combination of equal-diameter piers, according to the scaled-down model; the model pier diameter width D was 4.8 cm, the front and rea spacing was 8.6 cm, and the overall pier length was 24.3 cm, as shown in Figure 4 non-homogeneous sand with a median particle size of 0.51 mm and 0.63 mm (geom standard deviation [34] greater than 1.2) was laid at the bottom of the test section to ulate the riverbed conditions; the test was conducted under open-flow conditions an cover conditions for scour simulation, and under ice-cover conditions, polystyrene sheets (with a thickness of 3 cm) were used at the top of the test section to simula fixed ice cover. and the maximum scour depth around the pier during the test run.…”
Section: Computational Domain and Grid Informationmentioning
confidence: 99%
“…In order to avoid the sand bed at the entrance/exit boundary from being scoured by the approach flow, the high and wide scour prevention plates of equal height were laid in the front and rear sections of the model sand bed as the bed fixing area, and their surface roughness was consistent with that of the sand bed. The model of the bridge pier in the dynamic-bed test section for the field mea ments was based on the combination of equal-diameter piers, according to the scaled-down model; the model pier diameter width D was 4.8 cm, the front and rea spacing was 8.6 cm, and the overall pier length was 24.3 cm, as shown in Figure 4 non-homogeneous sand with a median particle size of 0.51 mm and 0.63 mm (geom standard deviation [34] greater than 1.2) was laid at the bottom of the test section to ulate the riverbed conditions; the test was conducted under open-flow conditions an cover conditions for scour simulation, and under ice-cover conditions, polystyrene sheets (with a thickness of 3 cm) were used at the top of the test section to simula fixed ice cover. and the maximum scour depth around the pier during the test run.…”
Section: Computational Domain and Grid Informationmentioning
confidence: 99%
“…There are complex turbulent vortices near the bottom bed of the bridge pier, and the sand initiation around the pier is influenced by the vortex motion; many scholars [35][36][37] have conducted a lot of investigations on the structural characteristics of the vortex system around the pier, and this paper focuses on the correlation between the vortex coherent structure, bed shear stress and sediment transport on the pier side under different scouring environments.…”
Section: Local Field Characteristicsmentioning
confidence: 99%
“…It is also confirmed that the zone of the maximum velocity tends to shift toward the mid-depth and closer to the channel bed. Considering the fact that flow structure around tandem piers or groups of piers is significantly different from single piers and scour depth around pile groups could exceed twice that of single piers [18]. Further research has focused on the study of peer groups, i.e., [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the fact that flow structure around tandem piers or groups of piers is significantly different from single piers and scour depth around pile groups could exceed twice that of single piers [18]. Further research has focused on the study of peer groups, i.e., [18,19]. Wang and Liang, 2020 introduced a new approach for calculating scour in layered soils based on the equilibrium concept and considering the geo-mechanical properties of the soils with different resistance to erosion.…”
Section: Introductionmentioning
confidence: 99%